Intranasal immunization with nontypeable Haemophilus influenzae outer membrane vesicles induces cross-protective immunity in mice. - Sandro Roier (PLoS ONE, 2012)
Haemophilus influenzae is a Gram-negative human-restricted bacterium that can act as a commensal and a pathogen of the respiratory tract. Especially nontypeable H. influenzae (NTHi) is a major threat to public health and is responsible for several infectious diseases in humans, such as pneumonia, sinusitis, and otitis media. Additionally, NTHi strains are highly associated with exacerbations in patients suffering from chronic obstructive pulmonary disease. Currently, there is no licensed vaccine against NTHi commercially available. Thus, this study investigated the utilization of outer membrane vesicles (OMVs) as a potential vaccine candidate against NTHi infections. We analyzed the immunogenic and protective properties of OMVs derived from various NTHi strains by means of nasopharyngeal immunization and colonization studies with BALB/c mice. The results presented herein demonstrate that an intranasal immunization with NTHi OMVs results in a robust and complex humoral and mucosal immune response. Immunoprecipitation revealed the most important immunogenic proteins, such as the heme utilization protein, protective surface antigen D15, heme binding protein A, and the outer membrane proteins P1, P2, P5 and P6. The induced immune response conferred not only protection against colonization with a homologous NTHi strain, which served as an OMV donor for the immunization mixtures, but also against a heterologous NTHi strain, whose OMVs were not part of the immunization mixtures. These findings indicate that OMVs derived from NTHi strains have a high potential to act as a vaccine against NTHi infections.